Document, Document, Document: The Value of the MOU - Christopher Jochum (Academic Chairpersons Conference Proceedings, 2020)
In this interactive session, the presenter will provide tips and lessons learned related to the power of documentation, especially through the use of memoranda of understanding (MOU). Equally applicable to faculty and students, participants will learn how to create MOUs and will be provided with examples and templates.
Keywords: Documentation; memorandum of understanding; conflict resolution; leadership development; department leadership